How risky is investment in human capital? - Joop Hartog; Hans van Ophem; Simona Maria Bajdechi (Center for Economic Studies and ifo Institute (CESifo), 2004)
The risk of investment in schooling has largely been ignored. We assess the variance in the rate of return by surveying the international empirical literature from this fresh perspective and by simulating risky earnings profiles in alternative options, choosing parameters on basis of the very limited evidence. The distribution of rates of return appears positively skewed. Our best guess of ex ante risk in university education is a coefficient of variation of about 0.3, comparable to that in a randomly selected financial portfolio with some 30 stocks. Allowing for stochastic components in earnings also markedly affects expected returns.
Keywords: J3; I2; 330; education; return; earnings dispersion; risk; Bildungsinvestition; Bildungsertrag; Risiko